If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2d = -1d + 10 Reorder the terms: -2d = 10 + -1d Solving -2d = 10 + -1d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add 'd' to each side of the equation. -2d + d = 10 + -1d + d Combine like terms: -2d + d = -1d -1d = 10 + -1d + d Combine like terms: -1d + d = 0 -1d = 10 + 0 -1d = 10 Divide each side by '-1'. d = -10 Simplifying d = -10
| xy(xy-u)= | | .75x+4.50=1.25x+2.50 | | 4k=3.6 | | 1/25:3=x:12 | | sinx=0.927 | | 3k=8+4k | | 2w=3w+10 | | -6=x-14+7x | | .5(6x+10)=20 | | q+70=55 | | -35-x=31+5x | | 3t+3=6t+9 | | (5x^2+1)(6x^2+4)=1 | | G/3=3.9 | | 3(x-5)-4(2x-3)=7 | | (2y+3y)2= | | x-.85x=32.89 | | 6a-10+5a=6a+20 | | 5+1.5(2m-1)=0.5 | | 5n+35+50=160 | | 58=1/2-x | | Sqrt(-7-7x)+3=10 | | 2/5x+1/10=1/2(x+4) | | 6a-10a+5a=6a+20 | | 58=1/2x | | 11pq(5p-7q+4)= | | 8x/4=12 | | -20+-3x=-12x+7 | | 1/2(4-x)=2/5 | | 43-n+16=44 | | 22=9+6(h+8) | | x-4=156 |